Eavesdropping on Referential Yellow Warbler Alarm Calls by Red-Winged Blackbirds Is Mediated by Brood Parasitism Risk - Lawson, Shelby L.; Enos, Janice K.; Gill, Sharon A.; Hauber, Mark E. (Frontiers in Ecology and Evolution, 2021)
Referential alarm calls that denote specific types of dangers are common across diverse vertebrate lineages. Different alarm calls can indicate a variety of threats, which often require specific actions to evade. Thus, to benefit from the call, listeners of referential alarm calls must be able to decode the signaled threat and respond to it in an appropriate manner. Yellow warblers (Setophaga petechia) produce referential “seet” calls that signal to conspecifics the presence of nearby obligate brood parasitic brown-headed cowbirds (Molothrus ater), which lay their eggs in the nests of other species, including yellow warblers. Our previous playback experiments have found that red-winged blackbirds (Agelaius phoeniceus), a species also parasitized by brown-headed cowbirds, eavesdrop upon and respond to yellow warbler seet calls during the incubation stage of nesting with aggression similar to responses to both cowbird chatters and predator calls. To determine if this hosts’ responses to seet calls vary with their own risk of brood parasitism, we presented the same playbacks during the nestling stage of breeding (when the risk of brood parasitism is lower than during incubation). As predicted, we found that redwings mediated their aggression towards both the cowbirds’ own chatter calls and the warblers’ anti-parasitic referential alarm calls in parallel with their current risk of brood parasitism (i.e., lower during the nestling stage). These results further support that red-winged blackbirds respond to yellow warbler antiparasitic referential calls as a frontline defense against brood parasitism at their own nests.